Tax neutrality: illusion or reality?: the case of entrepreneurship - Vesa Kanniainen; Paolo M. Panteghini (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper shows that taxes which are understood to be neutral with respect to the marginal investment decisions may be distortionary with respect to entrepreneurial decisions. In particular, we apply an intertemporal model to show that a comprehensive income tax is distortionary unless all kinds of income are subject to the same tax rate and a worker's option to become an entrepreneur is accounted for. Similarly, the harsh condition of a uniform tax rate is necessary but not sufficient under new view dividend tax, cash flow tax, and ACE tax, so that the occupational choice is not distorted. In any case, informational problems may arise and lead to distortive effects.
Keywords: H25; 330; ACE tax; cash flow tax; dividend tax; Johansson-Samuelson theorem; real options; Unternehmensplanung; Betriebliche Investitionspolitik; Steuerpolitik; Besteuerungsgrundsatz; Steuerwirkung; Unternehmer; Berufswahl; Theorie